Role of Soil and Vegetation in Hydrology - Qureshi, I. M.; Yadav, J. S. P.; Subba Rao, B. K.; Dabral, B. G. (Indian Forester, 1964)
Soil and water constitute by far the two most valuable natural resources and need to be protected from every loss. The various factors like inadequate vegetative cover, indiscriminate deforestation, excessive grazing, faulty cultivation, unsound agronomical practices, burning, defective land use, and neglect of soil conservation in the catchment areas of many rivers cause severe floods and run-off which result in tremendous damage. Excessive run-off whether it results in floods or not is by itself a wasteful phenomenon involving loss of both soil and utilisable water yield. The water balance of a watershed involving the various losses and gains has been explained. The importance of infiltration, percolation and storage capacity of the soil in governing the surface flow, sub-surface flow and base flow of precipitation has been dealt with. An account has been given of the effect of various soil characteristics on infiltration, percolation and storage capacity as well as water movement and hydrology of a given area. The harmful effects of burning, grazing and other faulty practices on the soil properties and hydrological conditions of a tract have been described. Important features of some common soil groups found in India having a bearing on their moisture relations have been mentioned. The value of soil moisture studies in understanding the water balance and in deciding suitable management practices to prevent floods and run-off has been emphasized. The effect of different vegetative covers on the soil properties, water movement and storage, interception, evapotranspiration, water yield, intensity of run-off and floods and such other aspects which are fundamental to the hydrological cycle of watersheds has been elucidated. The importance of the quality of water yield has been emphasized and has been correlated with the vegetative cover and with soil conditions. The beneficial role of the maintenance of a suitable vegetative cover in the control and prevention of floods has been examined. The protective and ameliorative functions of forests on steep slopes and undulating lands which are highly susceptible to quick run-off and easy soil wash have been emphasized. It has been stated that there is scarcity of scientific data on many such aspects in India. In view of the magnitude and complexity of the problem of run-off and floods the urgent necessity for a correct assessment of the exact requirements of each watershed in the light of varying climatic, edaphic and biotic conditions has been stressed so as to evolve most suitable management practices. An integrated approach to the study of hydro-meteorological elements with the cooperation of different research and administrative organisations in the country has been proposed.